The issue of sustainable land use in Ukraine taking into account the consequences of the war - Liudmyla Datsenko; Svitlana Titova; Marharyta Dubnytska; Oksana Kustovska (Acta Scientiarum Polonorum. Formatio Circumiectus, 2024)
Aim of the study: The purpose of the study is a consideration of theoretical and methodological issues of sustainable land use in Ukraine, taking into account the consequences of the war. The legal definition of sustainable land use is currently not well-grounded and balanced. In Ukraine today, the paradigm of sustainable (balanced) land use is still being formed, and the Land Policy Strategy for the management of land resources and land use should be based on it. The reasonable inclusion of institutionalization among the components of sustainable land use under the conditions of agreement on the conceptual basis of sustainable (balanced) land use consists in revealing the essence of the research component of the institutionalization of balanced land use, as a new paradigm for the use of land resources, taking into account the consequences of the war in Ukraine. Material and methods: The method of analysis is used to determine the possibilities of a more rapid development of the socially oriented market economy after the war. In our opinion, this can happen thanks to the deepening of the theoretical, methodological and methodical foundations of the rational use of land resources (the synthesis method), and optimization of the economic, social and ecological components of land use on the basis of their expansion at the expense of the institutionalization component (deduction method), which in turn will contribute to increasing the socio-economic efficiency of the use and reproduction of the productive potential of Ukraine’s lands in the post-war period (system approach). The theoretical basis consists of the scientific works of domestic and foreign scientists in the field of economics of nature use, land use and environmental protection; legislative and regulatory acts; methodological and instructional materials; and statistical and analytical data of ministries and departments of Ukraine – public organizations responsible for the use of land resources and socio-economic development regions of Ukraine. Monographic analysis – used for the study and generalization of existing scientific approaches to the problem of land use; to determine the essence of the complex concept of “sustainable land management” and its economic, social, and ecological components, and to justify management components of the institutionalization of balanced land use, based on the realities of today’s Ukraine, taking into account the possibilities of more rapid development of the social-oriented market economy after the war. The method of synthesis – applied due to its complex deepening of theoretical, methodological and methodical foundations of rational use of land resources, and optimization of economic, social and ecological components of land use on the basis of their expansion due to the components of institutionalization. It is substantiated that the methodology of institutionalization of sustainable land use with intensive exploitation of land (land resources) consists of the following: maintaining the necessary level of biotic regulation of land resources and the environment; and hierarchy of levels of management of sustainable land use, in particular: conceptual, ideological, political and economic. Structural and logical method – used to build a graphic-logistic model of the main components of land use as a social-ecological-economic system, as well as to find effective and rational ways to overcome the consequences of the war in Ukraine. The system approach is used not from the point of view of its structure, interrelationships and relations between individual components of sustainable land use, but from the aspect of systemic, economic and other land use, which was formed in the state under the influence of regulatory and legislative factors, with the aim of obtaining the highest effect from land use resource for compliance with the requirements for its reproduction and protection, which in turn will contribute to increasing the socio-economic efficiency of the use and reproduction of the productive potential of the lands of Ukraine in the post-war period. The land use system reveals an interconnected set of objects and subjects that function as a single whole in the natural environment, operating with information that is a product that comes from the environment, or a pragmatic part of structural information accumulated by the system itself. The research methodology is based on the following main principles: general dialectical principle of general connection and interaction; the principle of causality, which is connected with the principles of general connection and development; and principles of systematicity in cognition. Results and conclusions: At the current stage of development in Ukraine, the process of decentralization and territorial reorganization continues on the basis of sustainable territorial development. The implementation of such a concept aims at a radical change in the fundamental principles of social development management and is a prerequisite for solving various kinds of problems. The strategy and tactics of further institutional transformations in the field of land use, in our opinion, should consist in a gradual transition to such a type of land use organization that would ensure the creation of conditions for the rational and effective use of regional land potential, and economic and social stability of agricultural production. The essence of the research component of the institutionalization of balanced land use is presented. In particular, the transition to sustainable land use involves the formation of new reproductive relationships focused on meeting the ecological and resource needs of society. As a result, there is a natural need to build a corresponding subsystem of the national economy – sustainable (balanced) land use. It was determined that sustainable (balanced) land use should be understood as a system of organizing the use and protection of land and other natural resources and biodiversity and corresponding land relations corresponding to the relations of social development, in which the optimal ratio is achieved between social, ecological and economic factors of land use development, normalization of the qualitative state of land and other natural resources based on the introduction of an institutional component. A paradigm of views on sustainable land use is formulated, taking into account the consequences of the war in Ukraine.